Prevalence of Sleep Disorders in Patients With Knee, Hip and Hand Osteoarthritis: A Systematic Review With Meta-Analysis - Katrine Kindtler Krag-Andersen; Josephine Hauge van Zaane; Giovanna Laura Neves Antonio Gaban; Alessio Bricca; Paulo Ferreira; Michelle Hall; Henrik Bjarke Vaegter; Jonas Bloch Thorlund (Journal of Orthopaedic & Sports Physical Therapy, 2026)
OBJECTIVE: To estimate the pooled prevalences of insomnia, obstructive sleep apnea, restless legs syndrome, and narcolepsy in patients with knee, hip, or hand osteoarthritis. DESIGN: Prevalence systematic review with meta-analyses. The review protocol was pre-registered at PROSPERO (CRD420251005836). LITERATURE SEARCH: We conducted systematic searches in Embase, MEDLINE, and the Cochrane Library from inception to August 2025, supplemented by citation screening and reference checking. STUDY SELECTION CRITERIA: We identified observational and interventional studies reporting prevalence data on sleep disorders among patients with knee, hip, or hand osteoarthritis. DATA SYNTHESIS: Risk of bias was assessed using the Newcastle–Ottawa Scale, and certainty of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Pooled prevalence estimates were calculated using random-effects proportion meta-analyses, with subgroup analyses based on diagnostic criteria and patient characteristics. RESULTS: Eighteen studies (202,847 participants) were included (3 cohort, 5 case-control, 12 cross-sectional), of which 9 studies were of very good to good or high quality. Insomnia was the most prevalent sleep disorder (42% [95% CI: 34% to 51%]), followed by sleep apnea (37% [95% CI: 6% to 67%] and restless legs syndrome (35% [95% CI: 10% to 61%]). No studies reported on narcolepsy. Estimates varied by diagnostic criteria and sample characteristics across studies, and the certainty of evidence was very low. CONCLUSION: Sleep disorders, particularly insomnia, are common among patients with knee, hip, or hand osteoarthritis, supporting the need to raise clinical awareness. Future studies may alter prevalence estimates, as only a small number of high-quality studies were identified and large between-study heterogeneity was observed.